THE USE OF JKN MOBILE APPLICATION IN IMPROVING PATIENT SATISFACTION IN REGISTRATION SERVICES AT KAUMAN BARU HEALTH CENTER, PONOROGO REGENCY - Aisah Nur Rahmawati; Rumpiati Rumpiati (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Digital transformation in healthcare has encouraged the adoption of innovations, including the Mobile JKN application, which is designed to improve service efficiency and patient satisfaction during registration at healthcare facilities. This study aimed to analyze the relationship between Mobile JKN application use and patient satisfaction, identify factors influencing its utilization, and examine barriers encountered at Puskesmas Kauman Baru, Ponorogo Regency. A descriptive quantitative design was applied involving 50 respondents selected through purposive sampling. Data were collected using questionnaires, observations, and interviews, then analyzed descriptively and through the Spearman correlation test with SPSS software. The findings showed a significant relationship between the use of the Mobile JKN application and patient satisfaction, with a correlation coefficient of ρ = 0.318 and a significance value of p = 0.025. Mobile JKN use contributed positively to patient satisfaction because it provided easier access and greater time efficiency. This benefit was supported by the predominance of respondents aged 20–40 years, who were generally familiar with digital technology. Nevertheless, several barriers remained, including difficulties experienced by elderly users, technical problems, and limited internet network access. Therefore, education and adequate technical assistance are necessary to optimize Mobile JKN implementation and ensure equitable use across all age groups.